বিগত আট দশকে বাংলাদেশে দারিদ্র নিরসনে অর্জন ও অসম্পূর্ণতা : উন্নয়ন তত্ত্বের অগ্নিপরীক্ষা না অনিশ্চিত মহিমা ? - খান, আকবর আলি (BRAC University, 2016)
The Paper read out by Professor Akbar Ali Khan, Professor BBS in the workshop organized to celebrate Sir Abed's 80th Birthday at BRAC Centre Auditorium on 26 April 2016.